2014
DOI: 10.1186/1471-2334-14-216
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of antibody responses to trachoma antigens before and after mass drug administration

Abstract: BackgroundBlinding trachoma, caused by the bacteria Chlamydia trachomatis, is a neglected tropical disease targeted for elimination by 2020. A major component of the elimination strategy is mass drug administration (MDA) with azithromycin. Currently, program decisions are made based on clinical signs of ocular infection, but we have been investigating the use of antibody responses for post-MDA surveillance. In a previous study, IgG responses were detected in children lacking clinical evidence of trachoma, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 26 publications
5
64
2
Order By: Relevance
“…Serology has been suggested as a possible alternative to clinical signs and infection testing, as it indicates the cumulative exposure to Ct [19,20], with the potential to assess the impact of intervention efforts [21]. By monitoring the exposure to Ct of the youngest age groups, born after implementation of MDA, serology may prove useful for confirming that transmission has been interrupted [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serology has been suggested as a possible alternative to clinical signs and infection testing, as it indicates the cumulative exposure to Ct [19,20], with the potential to assess the impact of intervention efforts [21]. By monitoring the exposure to Ct of the youngest age groups, born after implementation of MDA, serology may prove useful for confirming that transmission has been interrupted [22].…”
Section: Introductionmentioning
confidence: 99%
“…Serology has recently been used in several studies [19,20,2224], three of which have taken place in districts that have completed three or more rounds of MDA [2224]. These studies have used the multiplex bead array platform (Bio-rad, Hercules, California) to detect antibodies against Pgp3 and CT694, antigens thought to be highly immunogenic [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, further work is needed to determine the half-life of Pgp3 antibodies and seroreversion rates. A previous study that examined a high-prevalence community before and after one round of azithromycin suggested that individual anti-Pgp3 antibody levels decreased slightly six months after drug treatment, but not enough to be considered seroreversion 51 . This is similar to results seen for urogenital Ct infection, where anti-Pgp3 antibody titres decreased over 4–7 years, but patients were still in the seropositive range 52 .…”
Section: Discussionmentioning
confidence: 98%
“…Antibodies to Pgp3 have recently been suggested for monitoring Ct transmission in trachoma programmes 10,29 , but there is still much to learn about the dynamics of these responses. For example, it is not clear whether anti-Pgp3 responses are detectable in all individuals previously infected with Ct, or if multiple exposures are required to develop sustained anti-Ct responses.…”
Section: Discussionmentioning
confidence: 99%